Results of SIMS, LTPL and temperature-dependent Hall effect measurements performed on Al-doped alpha-SiC substrates grown by the M-PVT method - Contreras, Sylvie; Zielinski, Marcin; Konczewicz, Leszek; Blanc, Caroline; Juillaguet, Sandrine; Müller, Ralf; Künecke, Ulrike; Wellmann, Peter; Camassel, J. (Materials Science Forum, 2006)
We report on investigation of p-type doped, SiC wafers grown by the Modified-Physical Vapor Transport (M-PVT) method. SIMS measurements give Al concentrations in the range 10(18) to 10(20) cm(-3), with weak Ti concentration but large N compensation. To measure the wafers' resistivity, carrier concentration and mobility, temperature-dependant Hall effect measurements have been made in the range 100-850 K using the Van der Pauw method. The temperature dependence of the mobility suggests higher Al concentration, and higher compensation, than estimated from SIMS. Additional LTPL measurements show no evidence of additional impurities in the range of investigation, but suggest that the additional compensation may come from an increased concentration of non-radiative centers.
Keywords: p-type bulk; Al doping; Hall effect; SIMS